Why do women watch esports? A social role perspective on spectating motives and points of attachment. (February 2022) - Yu, Bo; Brison, Natasha T.; Bennett, Gregg
Abstract: Guided by social role theory and the extant literature, the purpose of this investigation was to examine the gender differences in esports spectating motives and points of attachment. A questionnaire was developed to survey fans ( N  = 479) of the Houston Outlaws, a professional team in the Overwatch League. Findings indicate gender differences across five motivational factors: women seem to be more motivated to watch Overwatch for social opportunities, interest in player, and (player) physical attractiveness; men appear to be more motivated to watch for enjoyment of aggression and entertainment value. Our results also suggest how perceived social roles may influence gender differences in attachment to the athlete and its relationship with spectating motives. Theoretical, managerial, and social implications, as well as future research recommendations, are discussed. Highlights: The study compares men and women in their esports spectating motivations. Women watch esports for social opportunities, interest in player, and physical attractiveness. Men watch esports for enjoyment of aggression, and entertainment value. Interest in player were shown to positively impact attachment to the athlete for both men and women.